2012
DOI: 10.1111/j.1466-8238.2012.00764.x
|View full text |Cite
|
Sign up to set email alerts
|

How are tree species distributed in climatic space? A simple and general pattern

Abstract: Aim  Although many factors undoubtedly affect species geographic distributions, can a single, simple model nonetheless capture most of the spatial variation in the probability of presence/absence in a large set of species? For 482 North American tree species that occur east of the Rocky Mountains, we investigated the shape(s) of the relationship between the probability of occupancy of a given location and macroclimate, and its consistency among species and regions. Location  North America. Methods  Using Littl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
81
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(84 citation statements)
references
References 58 publications
3
81
0
Order By: Relevance
“…Regardless of their specific mechanism, top-down hypotheses of species richness predict that the richnessenvironment relationship is congruent through time and space because the mechanism operates independently of factors that vary spatially or temporally, other than climate [13]. In other words, these hypotheses require that the environment limits the number of species that can occur in a given region [13,14], or determines stochastic immigration and extinction rates [12,15].…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of their specific mechanism, top-down hypotheses of species richness predict that the richnessenvironment relationship is congruent through time and space because the mechanism operates independently of factors that vary spatially or temporally, other than climate [13]. In other words, these hypotheses require that the environment limits the number of species that can occur in a given region [13,14], or determines stochastic immigration and extinction rates [12,15].…”
Section: Introductionmentioning
confidence: 99%
“…The approach is innovative in combining a well-established technique in statistical niche modelling (multiple logistic regression, which is closely related to the popular maximum entropy method; Phillips et al, 2006) with algorithms used to estimate bioclimatic variables for dynamic vegetation and biogeochemistry modelling, and a process-based method to take account of CO 2 concentration effects. By fitting models with linear and quadratic (but not interaction) terms for each predictor, our modelling approach is consistent with Boucher-Lalonde et al (2012), who showed that the probabilities of occurrence of tree species in North America could be predicted with high efficiency from independent Gaussian functions of climate variables.…”
Section: Introductionmentioning
confidence: 59%
“…We were not able to include edaphic factors in our models because these are not known for the entire exposed Sunda Shelf. Nonetheless, plant distributions are primarily dictated by temperature and precipitation (31,42,43), within the climatic bounds modified by edaphic conditions. Even if the exposed region was fully covered by sandy soils, this still is no reason to assume that Dipterocarp rainforest was absent from central Sundaland.…”
Section: Resultsmentioning
confidence: 99%